Biomechanical Evaluation of Suture Button Spread with and without Deltoid Repair in Combined Syndesmosis and Deltoid Injury. Issue 4 (22nd October 2020) - Lau, Brian; Storaci, Hunter; Tam, Kaysie; Lai, Cara; Salazar, Brett P.; Guzman, Roberto; Oji, David E.; Chou, Loretta B.
Category: Sports; Basic Sciences/Biologics Introduction/Purpose: Syndesmosis injuries are common and frequently occur with deltoid injuries but optimal repair remains controversial. Prior biomechanical studies have demonstrated that 1 and 2 suture buttons are equivalent to screw fixation and that parallel or divergent suture buttons are equivalent to single suture button. Prior studies, however, created constructs with suture buttons within 1cm from each other (2-3cm from joint surface). Additionally, the role of deltoid injury and repair have not been evaluated in conjunction with syndesmosis injury and repair. The purpose of this study was to biomechanically compare a narrow vs spread 2-suture button construct with and without a deltoid repair. Methods: Four matched lower leg specimens (8 total specimens) aged mean 60.2 years (range 57-66 years; 6 females and 2 males; mean BMI 21.1) were tested. Ankle motion under cyclic loading was measured in multiple planes: first in the intact state, following simulated syndesmosis and deltoid injury, then following fixation with 1 of 2 randomly assigned constructs: 2 parallel suture buttons at 2 and 3cm from joint line (narrow); and 2 parallel suture buttons at 1 and 4cm from joint line (spread), and then finally following a deltoid repair with each construct. Each state was tested at a constant 750 N axial compressive force and 5N internal/external torque. Rotation position (degrees) and anterior-posterior displacement (mm) were collected throughout the testing to characterize relative spatial relationships of the tibiofibular articulation using 3D video capture technology. Results: Narrow and spread 2-suture button constructs improved rotation and translation compared to cut state (p<0.05) but not to intact state (p>0.05). There were no significant differences in rotation or translation between Narrow and Spread constructs (p>0.05). The addition of a deltoid repair did not improve rotation or translation compared to syndesmosis repair with either construct alone (p>0.05). Conclusion: The preliminary results of this study suggest that constructs with suture button placed close together or spread apart during fixation of combined syndesmosis and deltoid injury could improve rotation and translation equally. Additionally, in a combined syndesmosis and deltoid injury, the addition of a deltoid repair to a syndesmosis repair did not strengthen the construct. These findings suggest that repair of syndesmosis alone may be sufficient in combined syndesmosis and deltoid injuries. Additional matched samples will be tested to validate preliminary findings.